2014
DOI: 10.1007/s40142-014-0034-x
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Alzheimer’s Disease Genes and the Potentially Implicated Pathways

Abstract: Late-onset Alzheimer’s disease (LOAD) is a devastating neurodegenerative disease with no effective treatment or cure. In addition to APOE, recent large genome-wide association studies have identified variation in over 20 loci that contribute to disease risk: CR1, BIN1, INPP5D, MEF2C, TREM2, CD2AP, HLA-DRB1/HLA-DRB5, EPHA1, NME8, ZCWPW1, CLU, PTK2B, PICALM, SORL1, CELF1, MS4A4/MS4A6E, SLC24A4/RIN3,FERMT2, CD33, ABCA7, CASS4. In addition, rare variants associated with LOAD have also been identified in APP, TREM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 123 publications
2
127
2
1
Order By: Relevance
“…Remarkably, six of the susceptibility genes so far recovered from genome-wide association studies in Alzheimer's disease patients are p53 targets in neurons in our study: BIN1/Amph, PICALM/lap, CR1/CG10186, MEF2C/Mef2, SLC24A4/CG1090, and FERMT2/Fit1 (40,41). p53 may therefore play a critical role in regulating genes involved in Alzheimer's disease pathogenesis, correlating with the known up-regulation of p53 in the disorder (35,36).…”
Section: Genetic Validation Of a P53-dependent Pathway Involved Insupporting
confidence: 59%
“…Remarkably, six of the susceptibility genes so far recovered from genome-wide association studies in Alzheimer's disease patients are p53 targets in neurons in our study: BIN1/Amph, PICALM/lap, CR1/CG10186, MEF2C/Mef2, SLC24A4/CG1090, and FERMT2/Fit1 (40,41). p53 may therefore play a critical role in regulating genes involved in Alzheimer's disease pathogenesis, correlating with the known up-regulation of p53 in the disorder (35,36).…”
Section: Genetic Validation Of a P53-dependent Pathway Involved Insupporting
confidence: 59%
“…It has been implicated as a regulator of synapse formation [29], neural plasticity [30], and iron export [31]. Although APP was the first gene identified for early onset familial AD, only recently has a relationship between APP and LOAD been reported [32,33]. These results are in contrast to other studies that have not found associations between LOAD and common [34] or rare [35] APP SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…For a more extensive coverage of the literature, the interested reader is referred to excellent recent reviews (Holtzman et al, 2012; Kanekiyo et al, 2014; Mahley and Huang, 2012). In addition to APOE , recent large genome-wide association studies have identified over 20 loci that contribute to the risk of sporadic AD (reviewed in (Reitz, 2012; Rosenthal and Kamboh, 2014)). Several loci, such as CLU (clusterin or apoJ) and ABCA7 , are closely involved in the cholesterol metabolism pathway.…”
Section: Genetic Clinical and Experimental Evidence For Protective Ementioning
confidence: 99%